Pengaruh Etika Bisnis Islam dan Kualitas Produk Terhadap Loyalitas Nasabah PT. Bank SUMUT Syariah KCP Stabat - Nurfadilah, Nurfadilah; Saleh, Muhammad Saleh (Peduli Riset dan Pengabdian Masyarakat, 2023)
The research aims to determine the effect of Islamic business ethics and product quality on customer loyalty at PT. Bank SUMUT Syariah KCP Stabat. The source of this research data was obtained from the answers to the questionnaire given by the research respondents, namely PT. Bank SUMUT Syariah KCP Stabat as many as 100 respondents. Data analysis in this study used validity test, reliability test, classical assumption test, hypothesis test, and multiple linear regression analysis. Based on these tests, it is explained that there is a significant influence both partially and simultaneously between Islamic business ethics and product quality on customer loyalty at PT. Bank SUMUT Syariah KCP Stabat. Islamic business ethics and product quality affect customer loyalty at PT. Bank SUMUT Syariah KCP Stabat is 37,7% while the rest is influenced by other variables such as administrative costs, profit sharing ratios, promotions, locations, and others. There is a positive or in line meaning that if Islamic business ethics and product quality experience an increase, the customer loyalty of PT. Bank SUMUT Syariah KCP Stabat has also increased, and vice versa if Islamic business ethics and services have decreased, customer loyalty to PT. Bank SUMUT Syariah KCP Stabat decreased too.